Rastreabilidade bovina: vantagens e desvantagens da sua utilização - um estudo de casos múltiplos no município de Dom Pedrito - Quincozes, Adriana dos Santos (2015)
This paper addresses cattle traceability and its advantages and disadvantages. The use of this method was necessary because of foreign market requirements. In Brazil, cattle traceability is regulated by SISBOV (Brazilian System). The objectives of this study were to characterize the traceability method adopted, check critical issues faced by cattle raisers along the system implantation, and analyze the whole traceability process. According to the objectives, a qualitative and exploratory design has been adopted, and the method it was understood like a multiple case study involving three farmers from Dom Pedrito. The interviewees were selected due to their availability to provide private data related to their properties. The analysis has evidenced that cattle traceability adds value to beef and increases the differential between farmers that use the system. From the results, we can point out that farmers that have adhered to cattle traceability regard the method as a trigger to farm development that has several advantages, such as cattle control improvement and advantageous profits; as isadvantages, they mentioned unnecessary paperwork and bureaucracy. We have concluded that more farmers should adopt cattle traceability, as this would optimize the production chain and bring benefits such as higher profits and increased exports.